Lignocaine instilled through the suction channel of a subglottic suction drainage tracheal tube improves tube tolerance during extubation compared to intravenous lignocaine: A double-blinded randomised controlled trial - R Sripriya; Jyotsna Namburu; Ghansham Biyani; Nageswara Rao Tangirala; Vaishakh Tharavath; Raza S. Gouri (Indian Journal of Anaesthesia)
Background and Aims: Cough is frequently encountered during extubation. We propose a novel technique of utilising the suction port of a subglottic suction drainage endotracheal tube (SSD-ETT) to instil lignocaine around the cuff and improve tube tolerance during extubation. The primary objective was to assess the cough score during emergence. Secondary objectives included changes in haemodynamics and postoperative oropharyngeal morbidities. Methods: In total, 108 patients undergoing nasal surgery were tracheally intubated with the SSD-ETT and randomised to receive normal saline (NS) both intravenous and subglottic (Group C), subglottic NS and intravenous lignocaine (Group IVL), and subglottic lignocaine and intravenous NS (Group SGL) before reversal of residual neuromuscular blockade. The volume for subglottic administration was fixed at 3 mL of either 2% lignocaine or NS. The volume for intravenous administration was 1.5 mg/kg of 2% lignocaine or an equivalent volume of NS. Tube tolerance was graded using a 5-point qualitative cough score. Haemodynamics were recorded at baseline, post-intubation, and post-extubation. Postoperative oropharyngeal morbidities were also compared. Results: Seventy-five percent of patients in Group SGL had no cough, compared to 27.8% in Group IVL and 30% in Group C (P < 0.001). The heart rate immediately following extubation was significantly lower (P = 0.006) in Group SGL: 96 [standard deviation (SD): 19)] [95% confidence interval (CI): 90, 103] beats/min when compared with Group C: 107 (SD: 15) (95% CI: 102, 112) and Group IVL: 108 (SD: 18) (95% CI: 102, 114). The mean arterial pressure and oropharyngeal morbiditiy were comparable (P > 0.05). Conclusion: Subglottic instillation of lignocaine significantly improves tube tolerance during extubation and has favourable effects on heart rate compared to intravenous administration.